Pelatihan Pembuatan dan Pengelolaan Konten Website Untuk Meningkatkan Pelayanan Puskesmas Sungai Mariam - Nurhuda, Asep; Bagus Satria; Annafi Franz (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2023)
In today's digital era, many service institutions are digitalizing public services through internet media by presenting service delivery using websites. The existence of a website can save time and costs from people who want to communicate with service providers. As in this paper, Sungai Mariam Health Centre as a health service facility created a website to serve as a means of community service. In the process of making it, observation and problem analysis are carried out first so as to produce a website as needed. The advantages of the website that has been made are the features of activities outside the building, drug information and ask the pharmacist. Although the website was successfully made as expected, further research has not been carried out regarding the improvement of online-based services at Sungai Mariam Health Centre